2020
DOI: 10.11301/jsfe.20564
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of Co-Culture Biofilm Formed by <i>Lactobacillus plantarum</i> and <i>Pediococcus acidilactici</i>, and Antagonistic Effects of This Biofilm on Pathogen Growth

Abstract: Recent studies in lactic acid bacteria (LAB) biofilm formation have reported that the functional properties of LAB are associated with biofilm formation. In this study, Pediococcus acidilactici and Lactobacillus plantarum showed the ability to form a biofilm on a solid surface under static conditions. The morphology of LAB on MRS-CR agar showed that both P. acidilactici and L. plantarum could produce exopolysaccharide (EPS) on the cell surface which mainly contributed to forming the biofilm of single and co-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…Furthermore, in the co-culture condition, the viability, self-aggregation rate, adhesion to cells and biofilm formation of the bacteria were also have a relationship with each other during this special situation. In previous studies, it was found that co-cultured of L. plantarum and P. acidilactici VTCC 10800 or S. cerevisiae Y11-43 significantly improved the biofilm formation ability [38,39]. In addition, SEM results of biofilms under monoculture and co-culture conditions also confirmed this conclusion.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, in the co-culture condition, the viability, self-aggregation rate, adhesion to cells and biofilm formation of the bacteria were also have a relationship with each other during this special situation. In previous studies, it was found that co-cultured of L. plantarum and P. acidilactici VTCC 10800 or S. cerevisiae Y11-43 significantly improved the biofilm formation ability [38,39]. In addition, SEM results of biofilms under monoculture and co-culture conditions also confirmed this conclusion.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies found that cocultured L. plantarum and P. acidilactici VTCC 10800 or S. cerevisiae Y11-43 significantly improved the biofilm formation ability ( 32 , 33 ). In addition, biofilm detection results under monoculture and coculture conditions also confirmed this conclusion.…”
Section: Discussionmentioning
confidence: 94%
“…The EPS produced by L. acidophilus and Bifidobacterium animalis both had antioxidant activity in mono‐species culture, and the EPSs of their coculture had high thermal stability, maximum DPPH and hydroxyl radical scavenging activity, and reducing power when cheese whey was used for microbial fermentation (Amiri et al., 2019). In another study of LAB coculture biofilms, the coculture biofilm formed by L. plantarum and Pediococcus acidilactici had a thicker thickness and higher antimicrobial activities against all tested pathogens (Nguyen et al., 2020). In addition, some biofilm properties, such as viscoelastic properties of multispecies biofilms formed by B. licheniformis and Pseudomonas fluorescens in the dairy industry, are most likely to be contributed by dominant good biofilm formers, P. fluorescens , which have great adaptive and reproductive capabilities (Abriat et al., 2019).…”
Section: Formation Of Multispecies Biofilmsmentioning
confidence: 99%
“…Control of harmful microorganisms in biofilms is achieved by competition with probiotic bacteria. For instance, both P. acidilactici and L. plantarum could produce exopolysaccharide and form coculture biofilms, which increased their antagonistic effects against P. aeruginosa and S. typhimurium , especially under flow conditions (Nguyen et al., 2020). Bacteriocin extracts are often chosen as antibacterial agents; however, their antimicrobial action could be limited owing to the protective effect of biofilms.…”
Section: Application Conclusion and Prospectsmentioning
confidence: 99%